Antimicrobial activity of selected Malaysian plants - Ali, Abdul Manaf; El-Sharkawy, Saleh H.; Abdul Hamid, Junainah; Ismail, Nor Hardiani; Lajis, Md Nordin (Universiti Putra Malaysia Press, 1995)
Methanolic extracts of seventeen Malaysian plants were screened against fungi, including yeast and candida, as well as gram negative and gram positive bacteria. Antimicrobial activities were present in extracts prepared from Borreria latifolia, B. selidens, Hedyotis diffusa, H. nudicaulis, Morinda elliptica, M. umbellata (Rubiaceae), Sida rhombifolia (malvaceae) and Vitex ovata (Verbenaceae). Extracts from S. rhombifolia and B. latifolia showed exreptionally high activity against Candida albicans, Ca. intermedia, Aspergillus ochraceous, Cunninghamella clegans and Pseudomonas aeruginosa. However, only moderate activity was observed against Bacillus cereus, Ba. megaterium and Ca. Iipolyuca. Extracts from Calophyllum inophyllum (Guttiferae), Entada sp. (Leguminosae), Eclipta alba (Compositae), Dendrotrophe umbellata (Santalaceae), Cardiospermum halicacabum (Sapindaceae), Glochidion lutcscens and Euphorbia prunifolia (Euphorbiaceae) gave negative results.